2016
DOI: 10.1248/cpb.c15-01033
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cyclopropylacetyl-(<i>R</i>)-carnitine, a Unique Chemical Marker of the Fatally Toxic Mushroom <i>Russula subnigricans</i>

Abstract: A toxic mushroom, Russula subnigricans, causes fatal poisoning by mistaken ingestion. In spite of the potent bioactivity, the responsible toxin had not been identified for about 50 years since its first documentation. Recently, we isolated an unstable toxin and determined the structure. The slow elucidation was partly due to the instability of the toxin and also due to misidentification of R. subnigricans for similar mushrooms. To discriminate genuine Russula subnigricans from similar unidentified Russula spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…The ingestion of R. subnigricans causes vomiting and diarrhea, followed by severe upper body ache and hematuria. 105 In severe cases, it causes speech impediment, cardiac damage, loss of consciousness, and acute rhabdomyolysis. 106,107 Distinctively, this mushroom produces chlorinated phenyl ethers, russuphelins A-G (65-71), and a chlorohydroquinone tetramer russuphelol (72).…”
Section: Phenolicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ingestion of R. subnigricans causes vomiting and diarrhea, followed by severe upper body ache and hematuria. 105 In severe cases, it causes speech impediment, cardiac damage, loss of consciousness, and acute rhabdomyolysis. 106,107 Distinctively, this mushroom produces chlorinated phenyl ethers, russuphelins A-G (65-71), and a chlorohydroquinone tetramer russuphelol (72).…”
Section: Phenolicsmentioning
confidence: 99%
“…111 In 2016, Hashimoto et al identied unique naturally occurring compounds, including cyclopropylacetyl-(R)-carnitine (361) and 3-hydroxybaikiain (362) from R. subnigricans, along with 360, where it was proposed that 361 is specic to R. subnigricans since the upelded proton signals corresponding to the cyclopropane ring are easily detectable in the 1 H NMR spectrum of its crude extract. 356 In fact, 361 is very stable under normal isolation procedures and it can be useful as a chemical marker for the identication of genuine R. subnigricans.…”
Section: Miscellaneous Secondary Metabolitesmentioning
confidence: 99%
“…Both mycotoxins can cause potentially fatal rhabdomyolysis resulting in acute renal failure after consumption. [17][18][19] In 2001, French investigators reported 12 cases of delayed rhabdomyolysis with 3 fatalities in patients who had consumed consecutive meals of the edible wild mushroom Tricholoma equestre, harvested from pine forests in coastal southwestern France (Figure 4). 17 After a prodrome of afebrile fatigue and myalgia 24 to 72 h after the last mushroom meal, most (n=8) patients described worsening weakness and stiffness of their legs, accompanied by facial erythema, mild nausea without vomiting, profuse sweating, and darkening urine color over 3 to 4 d. 17 Rhabdomyolysis was later confirmed by significantly elevated CK levels without laboratory evidence of cardiac or hepatic injury.…”
Section: Rhabdomyolysis-causing Mushroomsmentioning
confidence: 99%
“…17 In 2016, Japanese investigators isolated a unique compound from R subnigricans mushrooms, cyclopropylacetyl-(R)-carnitine, which caused elevated CK levels in mice and was suspected to be the human myotoxin. 19 Visual and microscopic identification of poisonous mushrooms and their spores by experts may offer a more rapid means of identifying mushrooms as potentially nephrotoxic in the field than immunologic and chromatographic techniques in the laboratory. In 2012, Boston-based investigators reported 2 cases of hepatotoxic Amanita mushroom poisoning in Ukrainian immigrants in the Boston area; the authors attributed their successful supportive management to early identification of the ingested mushrooms as containing amatoxin via an initial cellphone image transmitted to a consulting poison control center mycologist.…”
Section: Identifying Nephrotoxins In Mushrooms and In Poisoned Patientsmentioning
confidence: 99%
“…The chemical constituents of several other mushrooms have been investigated, such as R. japonica , R. subnigricans , R. lepida , R. cyanoxantha , etc. [8,9,10,11]. R. vinosa has been used as a multifunctional edible food in our life and although there are some studies on the water-soluble polysaccharides, few systematic investigations on the fat-soluble components have been performed.…”
Section: Introductionmentioning
confidence: 99%